2012
DOI: 10.1152/jn.00739.2011
|View full text |Cite
|
Sign up to set email alerts
|

The influence of surround suppression on adaptation effects in primary visual cortex

Abstract: Wissig SC, Kohn A. The influence of surround suppression on adaptation effects in primary visual cortex. J Neurophysiol 107: 3370-3384, 2012. First published March 14, 2012 doi:10.1152/jn.00739.2011.-Adaptation, the prolonged presentation of stimuli, has been used to probe mechanisms of visual processing in physiological, imaging, and perceptual studies. Previous neurophysiological studies have measured adaptation effects by using stimuli tailored to evoke robust responses in individual neurons. This approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
145
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(163 citation statements)
references
References 83 publications
13
145
1
1
Order By: Relevance
“…Subsets of cells responding to repeated visual stimulation with sensitization have been described in the retina (Kastner and Baccus 2011), LGN (Camp et al 2009), and cortex (Wissig and Kohn 2012). Psychophysical experiments have demonstrated enhanced sensitivity following stimulus deprivation (Zhang et al 2009), which may be related to the increased spontaneous rate that we found after prolonged neuronal response suppression.…”
Section: Discussionsupporting
confidence: 65%
“…Subsets of cells responding to repeated visual stimulation with sensitization have been described in the retina (Kastner and Baccus 2011), LGN (Camp et al 2009), and cortex (Wissig and Kohn 2012). Psychophysical experiments have demonstrated enhanced sensitivity following stimulus deprivation (Zhang et al 2009), which may be related to the increased spontaneous rate that we found after prolonged neuronal response suppression.…”
Section: Discussionsupporting
confidence: 65%
“…Attentional modulation also involves normalization (Reynolds and Heeger, 2009;Sundberg et al, 2009;Lee and Maunsell, 2010;Ni et al, 2012;Schwartz and Coen-Cagli, 2013) and it too weakens correlations (Cohen and Maunsell, 2009;Mitchell et al, 2009). Finally, adaptation may affect normalization signals (Wainwright et al, 2002;Wissig and Kohn, 2012), and it also alters correlations (Gutnisky and Dragoi, 2008;Adibi et al, 2013). Note that although these many different forms of modulation have been cast as involving normalization, they may involve distinct cellular and circuit processes.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the weights of divisive normalization are optimized to improve the efficiency of sensory coding Wainwright et al, 2002;Sinz and Bethge, 2013). Divisive normalization (or gain control) has also been used to explain some adaptation phenomena (Ohzawa et al, 1982;Heeger, 1992b;Wainwright et al, 2002;Wissig and Kohn, 2012;Solomon and Kohn, 2014). The model that we propose updates the normalization weights between each pair of neurons based on the product of their responses and could be implemented by a simple synaptic mechanism for coincidence detection (Levy and Steward, 1983;Yao and Dan, 2001;Yao et al, 2004).…”
Section: Introductionmentioning
confidence: 99%